Investigação da influência do cochilo na aprendizagem escolar - Silva, Nathalia Maria Lemos da (2012)
There is a known positive effect of nocturnal sleep for brain plasticity and the consolidation of declarative and procedural memories, as well as for the facilitation of insight in problem solving. However, a possible pro-mnemonic effect of daytime naps after learning is yet to be properly characterized. The goal of this project was to evaluate the influence of daytime naps on learning among elementary and middleschool students, measuring the one-day (acute), and semester-long (chronic) effects of post-learning naps on performance. In the Acute Day-Nap condition, the elementary students were exposed to a class and then randomly divided into three groups: Nap (N), Game-based English Class (GBEC) and Traditional English Class (TEC). There were 2 multiple-choice follow-up tests to evaluate students performance in the short and long runs. In the short run, the N group outperformed the other two groups; and such tendency was maintained in the long run. In the chronic condition, the middle-school students were randomly separated into two groups: Nap (N) and Class (C) and were observed during one academic term. The N group had increased school performance in relation to the C group. In the statistical analyses, independent t-tests were applied considering the scores significant when p<0,05, expressed in terms of average ± average standard error. Results can be interpreted as an indication that a single daytime nap opportunity is not enough to ensure learning benefits. Therefore, more research is needed in order to advocate in favor of a daytime nap as a pedagogical means of promoting enhanced school performance